VD_FINDINFO HC / 2022 / 147 vom 24. Januar 2022 - VD Tribunal cantonal (2022)
CONVENTION{SIGNIFICATION ET NOTIFICATION DES ACTES JUDICIAIRES}, RÉPUDIATIONDROIT SUCCESSORAL, RESTITUTION DU DÉLAI | 576 CC, 138 al. 1 CPC (CH), 5 CLaH 65